Two or three days of ofloxacin treatment for uncomplicated multidrug-resistant typhoid fever in children. - Vinh, H; Wain, J; Vo, T; Cao, N; Mai, T; Bethell, D; Nguyen, T; Tu, S; Nguyen, MD; White, N (1996)
An open randomized comparison of 2 days (Ofx2) versus 3 days (Ofx3) of oral ofloxacin treatment (15 mg/kg/day) was conducted with Vietnamese children between 1 and 15 years of age with suspected typhoid fever. Of 108 children enrolled, 100 were blood culture positive for Salmonella typhi, and 86% of the isolates were multidrug resistant. There were no significant adverse effects. The therapeutic responses were similar in both groups, with mean (+/- standard deviation) fever clearances of 107 +/- 60 h in the Ofx3 group and 100 +/- 64 h in the Ofx2 group (P > 0.2). There were six "clinical" failures in the Ofx2 group and two clinical failures in the Ofx3 group (P > 0.2), in which fever and symptoms persisted for more than 1 week after the start of treatment, but only one of these was culture positive (Ofx3). There was one suspected relapse, and one carrier was identified. Short courses of ofloxacin are simple, inexpensive, safe, and effective for the treatment of uncomplicated multidrug-resistant typhoid fever.